If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11(-4b-5)+9=8b-3(-6-4b)
We move all terms to the left:
11(-4b-5)+9-(8b-3(-6-4b))=0
We add all the numbers together, and all the variables
11(-4b-5)-(8b-3(-4b-6))+9=0
We multiply parentheses
-44b-(8b-3(-4b-6))-55+9=0
We calculate terms in parentheses: -(8b-3(-4b-6)), so:We add all the numbers together, and all the variables
8b-3(-4b-6)
We multiply parentheses
8b+12b+18
We add all the numbers together, and all the variables
20b+18
Back to the equation:
-(20b+18)
-44b-(20b+18)-46=0
We get rid of parentheses
-44b-20b-18-46=0
We add all the numbers together, and all the variables
-64b-64=0
We move all terms containing b to the left, all other terms to the right
-64b=64
b=64/-64
b=-1
| -5(3x-13)=2(x-21)-29 | | -16w-1=-20-17w | | 7+3h=4h | | 8•4•k+9•5=(36-4)k-(2•5) | | 6(5x-30)+2=14 | | 14+18q=2+18+19q | | 5=12x-4 | | v+2.2=5.43 | | 7-2y=37 | | 4-(x+9)=-3(x-5) | | w-3.6=8.66 | | 1/2(x-160=5+7x | | x+2.4=9.15 | | 7h=-20+8h | | 10(x-8)=14 | | 16-1/5(x+10)=9 | | -18-13f=2-12f | | 5r^2-28r+15=0 | | 19=3x-11 | | 19+3x=4(-x+3)-49 | | −8.5x+0.54=−2.86 | | 8(10n-4)=6+80n | | 4v+14=82 | | 5(x+8)=8(X-1) | | -2m=10−7m | | -3c÷8=6 | | 14-m=9m-12m-16 | | -7v+3(v+3)=-11 | | 8x-32=4x-64 | | -7v+3(3+v)=-11 | | 15b=-17-2b | | 74-1,4t=62-0,2 |